KONTEKS KE-INDONESIA-AN DALAM TAFSIR AL-MISHBAH KARYA M. QURAISH SHIHAB - Siar Nimah; Ahmad Mujahid; Firdaus; Amir Hamzah (LP2M IAIM Sinjai, 2024)
This research tries to reveal how the Indonesian context of Tafsir al-Misbah is an inseparable part of the meaning of the text, also strengthened by the adabi ijtima'i style it carries. To reveal this meaning, it was chosen QS. Ar-Rum/30 verse 21 as the object of the study. As a text study, this research uses library research by conducting content analysis of the interpretive content. Finally, this research provides initial conclusions as follows: 1) Meaning of QS. Ar-Rum/30: 21 regarding the marriage bond with mawaddah and rahmah, especially when describing the diction 'mawaddah' shows a depiction that is very close to the social and even psychological conditions of Indonesian people, 2) The depiction in question is 'the husband's willingness to defend wife and the wife's willingness to follow her husband with a willingness to leave parents and family', this phrase includes conditions and sentences that are often described in the close relationship between husband and wife in the context of Indonesian society, 3) The choice of depiction of meaning according to the Indonesian context is very relevant considering the main reader from Tafsir Al-Misbah are Indonesian people, thus further strengthening the Indonesian side of the interpretation.